1978
DOI: 10.1111/j.1365-2621.1978.tb07411.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Further Lipid Peroxidation in the Distillation 2‐thiobarbituric Acid Test of Fish and Meat

Abstract: The effect of adding propyl gallate (PG) and ethylenediaminetetraacetic acid (EDTA) in the distillation 2-thiobarbituric acid (TBA) test of fish and meat samples was determined with the purpose of minimizing further oxidation of lipids during the test. Alsddeiermined was the effect of chilled blending on TBA values. The addition of PC and EDTA to the distillation mixture substantially lowered TBA values of catfish samples, while it did not show any significant effect on beef, pork, and chicken samples. Chilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
10

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 16 publications
2
114
0
10
Order By: Relevance
“…The results obtained in the present study contrast with those reported by Pikul et al (1989), Witte, Krause, and Bailey (1970), Vyncke (1975), and Salih et al (1987), who reported that DM procedures generally lead to higher TBA-RS numbers than EM. Rhee (1978) attributed the higher TBA-RS numbers from DM to the thermal decomposition of MDA precursors during distilation and its liberation by heat from its bound state with proteins. In those works, the distilation of MDA is performed on the meat samples, which generally leads to additional formation of MDA and an overestimation of TBA-RS numbers (Pikul et al, 1983;Siu & Draper, 1978;Witte et al, 1970).…”
Section: Tba-mda Adductmentioning
confidence: 97%
“…The results obtained in the present study contrast with those reported by Pikul et al (1989), Witte, Krause, and Bailey (1970), Vyncke (1975), and Salih et al (1987), who reported that DM procedures generally lead to higher TBA-RS numbers than EM. Rhee (1978) attributed the higher TBA-RS numbers from DM to the thermal decomposition of MDA precursors during distilation and its liberation by heat from its bound state with proteins. In those works, the distilation of MDA is performed on the meat samples, which generally leads to additional formation of MDA and an overestimation of TBA-RS numbers (Pikul et al, 1983;Siu & Draper, 1978;Witte et al, 1970).…”
Section: Tba-mda Adductmentioning
confidence: 97%
“…For example, Moerck and Ball (1974) suggested that Tenox II be added to the distillation mixture prior to heating in order to retard further oxidation and consequently artefact formation during this step, while Ke et al (1977) reported the use of propyl gallate (PG) and ethylenediaminetetraacetic acid (EDT A) during distillation for this purpose. However, researchers have pointed out that some phenolic antioxidants such as butylated hydroxyanisole (BHA) used in order to retard further oxidation of samples may in fact enhance the decomposition of lipid peroxides during distillation (Rhee, 1978a). Recently Shahidi and Hong (1991) showed that addition of commonly used antioxidants and chelators has a marginal effect in prevention of further lipid oxidation of meat lipids during the distillation step.…”
Section: -Thiobarbituric Acid Testmentioning
confidence: 99%
“…The thiobarbituricacid (TBA) test measures malonaldehyde (MDA) formation, and it is a colorimetric method (measures color intensity), in which the absorbance of a red chromogen (color) formed between TBAV and MDA is measured at 530 nm (Rhee, 1978;Pokorny et al,1989).Color intensity is correlated with the degree of rancidity. The test involves primarily a reaction of TBA with malonic dialdehyde by heating in the presence of a strong acid to give a red coloration.…”
Section: Laboratory Analysismentioning
confidence: 99%